2013
DOI: 10.1088/0067-0049/208/2/26
|View full text |Cite
|
Sign up to set email alerts
|

The Abundances of Hydrocarbon Functional Groups in the Interstellar Medium Inferred From Laboratory Spectra of Hydrogenated and Methylated Polycyclic Aromatic Hydrocarbons

Abstract: Infrared (IR) absorption spectra of individual polycyclic aromatic hydrocarbons (PAHs) containing methyl (-CH 3 ), methylene ( CH 2 ), or diamond-like CH groups and IR spectra of mixtures of methylated and hydrogenated PAHs prepared by gas-phase condensation were measured at room temperature (as grains in pellets) and at low temperature (isolated in Ne matrices). In addition, the PAH blends were subjected to an in-depth molecular structure analysis by means of high-performance liquid chromatography, nuclear ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 62 publications
(119 reference statements)
1
39
0
Order By: Relevance
“…A final feature of interest is the 3.40-µm feature on the 3-µm plateau. Several explanations have been put forward to account for its presence ranging from hot bands of aromatic CH-stretch transition υ = 2 → 1 shifted due to anharmonic effects (Barker et al 1987) to CH-stretch modes in methylated (Joblin et al 1996;Pauzat et al 1999) and superhydrogenated (Bernstein et al 1996;Steglich et al 2013;Sandford et al 2013;Wagner et al 2000) PAHs , but none of these have so far been confirmed. The overall picture that emanates from our high-resolution studies, involving in particular the role of anharmonicity, suggests that an explanation based on hydrogenated and alkylated PAHs is attractive.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…A final feature of interest is the 3.40-µm feature on the 3-µm plateau. Several explanations have been put forward to account for its presence ranging from hot bands of aromatic CH-stretch transition υ = 2 → 1 shifted due to anharmonic effects (Barker et al 1987) to CH-stretch modes in methylated (Joblin et al 1996;Pauzat et al 1999) and superhydrogenated (Bernstein et al 1996;Steglich et al 2013;Sandford et al 2013;Wagner et al 2000) PAHs , but none of these have so far been confirmed. The overall picture that emanates from our high-resolution studies, involving in particular the role of anharmonicity, suggests that an explanation based on hydrogenated and alkylated PAHs is attractive.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…In many interstellar and circumstellar environments the 3.3 µm emission feature is indeed often accompanied by a weaker feature at 3.4 µm (see Li & Draine 2012 and references therein). As demonstrated by Li & Draine (2012) and Yang et al (2013), one can place an upper limit of ∼ 2% on the aliphatic fraction of the emitters of the UIE features by assigning the 3.4 µm emission exclusively to aliphatic C-H (also see Rouillé et al 2012, Steglich et al 2013. This is indeed an upper limit as the 3.4 µm emission feature could also be due to anharmonicity of the aromatic C-H stretch (Barker et al 1987) and "superhydrogenated" PAHs whose edges contain excess H atoms (Bernstein et al 1996, Sandford et al 2013.…”
mentioning
confidence: 95%
“…In recent years, the aliphatic fraction of the UIE carriers -the ratio of the number of C atoms in aliphatic units (N C,ali ) to that in aromatic rings (N C,aro ) -has received much attention (e.g., see Kwok & Zhang 2011, Li & Draine 2012, Rouillé et al 2012, Steglich et al 2013, Yang et al 2013, 2016a. Kwok & Zhang (2011) argued that the material responsible for the UIE features may have a substantial aliphatic component and therefore, by definition, PAHs can not be the UIE carrier.…”
Section: Introductionmentioning
confidence: 99%